THE INFLUENCE OF EFFECTIVE LEADERSHIP AND ORGANIZATIONAL JUSTICE ON ORGANIZATIONAL COMMITMENT IN THE TRANSPORTATION INFRASTRUCTURE SECTOR OF THE SURABAYA CITY TRANSPORTATION SERVICE - Adhi Turnawan; Agus Ariyanto; Wido Untoro; Fariz Fariz (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The aim to be achieved in this research is for effective leadership and organizational justice to have a simultaneous influence on organizational commitment in the Transportation Infrastructure Sector of the Surabaya City Transportation Service. In accordance with the results of this research, it can be concluded that factors consisting of effective leadership and organizational justice have a significant and positive influence simultaneously on organizational commitment in the Transportation Infrastructure Sector of the Surabaya City Transportation Service. Factors consisting of effective leadership and organizational justice have a significant and partially positive influence on organizational commitment in the Transportation Infrastructure Sector of the Surabaya City Transportation Service. Among the factors consisting of effective leadership and organizational justice, it turns out that effective leadership has a dominant influence on organizational commitment in the Transportation Infrastructure Sector of the Surabaya City Transportation Service, with a partial influence of 63%. As input, we can provide a few suggestions that can be proposed for improving management which are implications of the research results, including: Encouraging transformational leadership behavior that inspires and motivates employees to achieve organizational goals, focus on building trust, fostering creativity, and empowering team members to contribute meaningfully, prioritize clear and transparent communication to ensure employees understand organizational goals, expectations and changes.